Synthesis of an Anion-Exchange Membrane Based on Imidazolium-Type Ionic Liquids for a Capacitive Energy Extraction Donnan Potential Device - Young-Seok Kim; Seong-Ho Choi (Journal of Chemistry)
Polymeric anion-exchange membranes (AEMs) were synthesized via the photocopolymerization of a vinyl imidazolium ionic liquid, with 1-butyl-3-(4-vinylbenzyl)imidazolium chloride ([BVBI][Cl]) as the anion-exchange group and styrene, acrylonitrile, and divinylbenzene as cross-linked agents. The physical, mechanical, and electrochemical properties of the prepared AEMs such as water uptake (%), swelling degree (%), ion-exchange capacity (mmol/g), thermal stability, tensile strength (Mpa), tensile modulus (Mpa), elongation (%), and ionic conductivity (S/cm) were evaluated. The synthesized AEMs were shown to have good physical, mechanical, and electrochemical properties for application of a capacitive energy extraction Donnan potential (CDP) device membrane. The CDP device was fabricated by using the synthesized AEM. The specific capacitance of the CDP device with AEM was determined as 2.53 F/g and 3.44 F/g by galvanostatic charge/discharge and cyclic voltammetry, respectively. The synthesized AEM with imidazolium ionic liquid can be applied as the CDP device membrane.